History And Clinical Examination Based Screening For Risk Factors Of Cardiovascular Diseases In A Cohort Of Final Year Medical Students Of Rawalpindi Medical University - Alisha Inayat, Mariam Agha, Maham Khalid, Rashid Naeem Khan, Maira Aslam, Alisha Inayat, Mariam Agha, Maham Khalid, Rashid Naeem Khan, Maira Aslam (Students’ Supplement of Journal of Rawalpindi Medical College, 2022)
Background: Cardiovascular diseases are the major cause of death all over the world. Various anthropometric measurements and family history can be used for screening and thus early detection and prevention of cardiovascular diseases. This study determines the risk factors of cardiovascular diseases, through history and clinical examination based screening, in final year MBBS students of Rawalpindi medical university. Methodology: It is an observational crosssectional study conducted on final year students of Rawalpindi Medical University. 106 students, 74.5% females and 25.5% males, were included in the study with mean age of 22 years. A self-devised questionnaire was used for data collection. Body Mass Index (BMI), Waist-to-Hip Ratio (WHR), Waistto-height Ratio (WHtR), blood pressure and family history of cardiovascular diseases were used to evaluate the risk of cardiovascular diseases in the participants. Results: Data analysis revealed that 68.9% participants had low risk, 30.2% had moderate risk and 0.9% had high risk to develop cardiovascular diseases. Conclusions: The study shows that all the above variables have positive association with the risk of cardiovascular diseases among which BMI, WHtR and WHR are most significant. Key words: Cardiovascular diseases, screening, Body Mass Index, Waist-to-height Ratio (WHtR), Waist-to-Hip Ratio (WHR), Blood pressure, family history, Ischemic Heart Disease (IHD), Diabetes mellitus, Stroke, PVD, Hypertension, Dyslipidemias.